Causal effects of world crude oil prices on the prices of rice and soybean oil: an ARDL approach - Abdul Samad, Abdul Rahim; Mohd Ashhari, Zariyawati (Universiti Putra Malaysia Press, 2011)
This study was undertaken to examine the impact of world crude oil prices on the prices of rice and soybean oil. Autoregressive Distribution Lag (ARDL) method was employed to investigate both the short-run dynamic and long-run relationship. All of the data were the time series annual basis from 1970 to 2008. The results revealed that the long-run relationship between world crude oil prices and rice prices did exist. In addition, the analysis also suggested that crude oil prices formed a major factor in the operation cost for the rice production in Malaysia. Nevertheless, the impact of crude oil prices did not only affect the direct cost in rice production but it also influenced the price of other materials required for rice production such as fertilizers.